Realization effects of enforcing the EU regulation on the installation of recording equipment in vehicles - Limba, Rimas; Lazauskas, Jonas (Transport, 2002)
Preparing to become a member of the European Union Lithuania will have to keep the requirements of the EU Regulation 3821/85 EEC in road transport. It concerns the installation of recording equipment in the vehicles of international transportation and local passenger and freight transport. According to the EU Regulation recording equipment (tachographs) must not be installed in every vehicle and it will be done step by step. About 38 thousand of vehicles will have operating tachographs and for four years it will require about 8 million Lt of investments per year, but the conditions of work and rest of drivers will be improved and the number of accidents will be decreased. First Published Online: 19 Dec 2011